Composite powder, skin external application composition, and method for enhancing fluorescence intensity of inorganic fluorescent powder

By coating inorganic fluorescent powders with non-fluorescent powders, the composite powder achieves enhanced luminescence and makeup effects, addressing the limitations of existing fluorescent powders in cosmetics.

JP7602861B2Active Publication Date: 2024-12-19ROHTO PHARM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2018200695
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-10-25
Publication Date
2024-12-19
Estimated Expiration
2038-10-25

AI Technical Summary

Technical Problem

Existing fluorescent powders used in cosmetics lack sufficient luminescence intensity and are not suitable for enhancing gloss or providing color correction effects, requiring high amounts to be effective.

Method used

A composite powder is formed by coating at least a portion of the surface of an inorganic fluorescent powder with a non-fluorescent powder, specifically using inorganic fluorescent powders with crystal hosts and activators like Al, Zn, Mg, Si, Mn, Ca, Ti, Ce, Ba, O, P, S, and non-fluorescent powders such as titanium oxide, zinc oxide, iron oxide, and silica, with a weight ratio of 95:5 to 70:30.

Benefits of technology

The composite powder significantly enhances fluorescence intensity, providing excellent luminescence and makeup effects, suitable for cosmetics and other applications like lighting and paints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602861000007
    Figure 0007602861000007
  • Figure 0007602861000008
    Figure 0007602861000008
  • Figure 0007602861000001
    Figure 0007602861000001
Patent Text Reader

Abstract

To provide a novel method for enhancing fluorescence intensity of an inorganic phosphor, and an inorganic phosphor having enhanced fluorescence intensity, obtained by using the method, and an external composition for skin containing the same.SOLUTION: At least a part of the surface of inorganic fluorescent powder is coated with non-fluorescent powder, to enhance fluorescence intensity of the inorganic fluorescent powder.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite powder of an inorganic fluorescent powder and a non-fluorescent powder, a skin external application composition containing the same, and a method for enhancing the fluorescence intensity of an inorganic fluorescent powder. [Background technology]

[0002] Cosmetics contain various powders depending on the purpose. In particular, in makeup cosmetics and sunscreen cosmetics, powders are generally used to impart effects such as gloss, soft focus properties, color correction, and ultraviolet protection properties.

[0003] Among powders, fluorescent powders are generally used in applications such as displays, lighting, playground equipment, and paints, but are also used in cosmetics to enhance makeup effects. For example, the use of fluorescent powders in cosmetics can impart not only soft focus properties, but also color correction effects due to the fluorescent color.

[0004] Patent Document 1 discloses a cosmetic that improves soft focus by including an inorganic fluorescent powder, an aluminate complex oxide. Patent Document 2 discloses a blue fluorescent powder that includes amorphous silica particles, and describes its application to cosmetics. However, the fluorescent powders described in Patent Documents 1 and 2 do not have sufficient luminescence intensity, so they need to be mixed in large amounts to be effective as cosmetics. In addition, these fluorescent powders have high soft focus properties, so they are not suitable for cosmetics that have the effect of enhancing luster.

[0005] In such a situation, a technology has been developed for enhancing the makeup effect by enhancing the fluorescence intensity of fluorescent powder. For example, Patent Document 3 discloses a cosmetic product in which the luminescence intensity is more effectively enhanced by containing an inorganic fluorescent powder and other powders. However, the technology described in this document may not be sufficient in enhancing the fluorescence intensity of the fluorescent powder.

[0006] Meanwhile, various composite powders are used in the field of cosmetics, and it is known that various cosmetic effects can be obtained by combining composite powders, etc. For example, Patent Document 4 discloses a composite powder that enhances the soft focus effect by compounding silica on an inorganic powder using a specific method. Patent Document 5 discloses a composite powder that enhances luster by compounding boron nitride with a metal oxide.

[0007] However, Patent Documents 4 and 5 do not contain any description of fluorescent powders, and the problem of enhancing the fluorescent intensity of fluorescent powders cannot be solved by referring to these documents. In addition, there is no description of the color correction effect. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-5255 A [Patent Document 2] JP 2016-141780 A [Patent Document 3] International Publication No. 2017 / 142057 [Patent Document 4] JP 2015-113306 A [Patent Document 5] JP 2011-236137 A Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a novel method for enhancing the fluorescence intensity of an inorganic fluorescent substance, an inorganic fluorescent substance having enhanced fluorescence intensity obtained using this method, and a cosmetic preparation containing the same. [Means for solving the problem]

[0010] As a result of extensive research conducted by the present inventors to solve the above problems, it was found that the fluorescence intensity can be increased by covering at least a portion of the surface of an inorganic fluorescent powder with a non-fluorescent powder.

[0011] That is, the gist of the present invention is as follows.

[0012] [1] A composite powder comprising a) an inorganic fluorescent powder and b) a non-fluorescent powder covering at least a portion of the surface of the inorganic fluorescent powder. [2] a) The composite powder according to [1], characterized in that the fluorescent wavelength of the inorganic fluorescent powder is within the range of 440 nm to 520 nm or 640 nm to 700 nm. [3] a) The composite powder according to [1] or [2], characterized in that the inorganic fluorescent powder contains at least one element selected from Al (aluminum), Zn (zinc), Mg (magnesium), Si (silicon), Mn (manganese), Ca (calcium), Ti (titanium), Ce (cerium), Ba (barium), O (oxygen), P (phosphorus), and S (sulfur) as a crystal matrix and / or an activator. [4] a) The composite powder according to any one of [1] to [3], characterized in that the inorganic fluorescent powder is at least one selected from the group consisting of (Al / Ca / manganese) oxide, (Mg / manganese / titanium) oxide, zinc oxide phosphor, and (Ca / cerium) phosphate. [5] b) The composite powder according to any one of [1] to [4], characterized in that the non-fluorescent powder is at least one selected from the group consisting of titanium oxide, non-fluorescent zinc oxide, iron oxide, aluminum oxide (alumina), and silica. [6] The composite powder according to any one of [1] to [5], wherein a particle size of the inorganic fluorescent powder is 1 μm or more and 200 μm or less. [7] b) The composite powder according to any one of [1] to [6], wherein the particle size of the non-fluorescent powder is 1 nm or more and 100 nm or less. [8] The composite powder according to any one of [1] to [7], characterized in that the ratio of a) inorganic fluorescent powder and b) non-fluorescent powder in the composite powder is component a:component b=95 (weight%):5 (weight%) to 70 (weight%):30 (weight%). [9] The composite powder according to any one of [1] to [8], which is for use in a composition for external application to skin.

[10] A composition for external use on the skin, comprising the complex powder according to any one of [1] to [9].

[11] A method for enhancing fluorescence intensity of an inorganic fluorescent powder, comprising: a) covering a portion of a surface of the inorganic fluorescent powder with b) a non-fluorescent powder. Effect of the Invention

[0013] According to the present invention, by forming a composite powder in which at least a portion of the surface of a) inorganic fluorescent powder is coated with b) non-fluorescent powder, the fluorescence intensity of a) inorganic fluorescent powder can be significantly improved. Furthermore, since the composite powder of the present invention in which at least a portion of the surface of a) inorganic fluorescent powder is coated with b) non-fluorescent powder exhibits excellent luminescence, by adding it to a cosmetic product, a cosmetic product with a stronger makeup effect can be provided. [Brief description of the drawings]

[0014] [Figure 1] 1 is a scanning electron microscope image of the inorganic fluorescent composite powder of Example 1. [Diagram 2] 1 is a scanning electron microscope image of the inorganic phosphor powder mixture of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described in detail. In addition, the terms used in this specification are to be interpreted as having the meanings usually used in the technical field unless otherwise specified.

[0016] Furthermore, % used in this specification refers to % by weight unless otherwise specified.

[0017] <Composite powder> The composite powder of the present invention is characterized in that at least a part of the surface of a) inorganic fluorescent powder is covered with b) non-fluorescent powder. Here, "covered" means that at least a part of the surface of a) inorganic fluorescent powder is covered with b) non-fluorescent powder, and includes both a) a part of the surface of inorganic fluorescent powder and a) the entire surface of inorganic fluorescent powder. The coverage of the composite powder of the present invention is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more.

[0018] The coverage rate in the present invention refers to the ratio of the difference between the surface area of ​​a) the inorganic fluorescent powder and the surface area of ​​the uncoated surface in the composite powder to the surface area of ​​a) the inorganic fluorescent powder, and can be expressed by the following formula.

number

[0019] A method for determining the coverage rate includes, for example, observing the surface of the composite powder in a scanning electron microscope image, determining the surface area of ​​the entire surface of the composite powder and the surface area of ​​the surface not covered with non-fluorescent powder by image analysis or the like, calculating the coverage rate of each composite powder using the above formula, and using the average of the coverage rates of multiple composite powders as the coverage rate of the composite powder in the present invention.

[0020] The inorganic fluorescent powder a) used in the present invention may be any inorganic powder having fluorescent properties, and there are no limitations on its shape or size.

[0021] a) The inorganic fluorescent powder may be an inorganic powder having fluorescent properties, and may be an inorganic fluorescent powder having fluorescent properties in the crystal matrix alone without an activator, or an activated phosphor consisting of a crystal matrix and an activator (impurity). The crystal matrix in this specification may be a crystalline or amorphous body. It may or may not contain other activators, and even when it does not contain an activator, it is used in the same sense as the commonly used crystalline and amorphous bodies. Examples of the crystal matrix include metal oxides, phosphate compounds, metal sulfides, metal sulfates, and halophosphate compounds, and metal oxides or phosphate compounds are preferred.

[0022] The crystalline host of the inorganic fluorescent powder a) used in the present invention preferably contains one or more elements selected from Al (aluminum), Ti (titanium), Zn (zinc), Ge (germanium), Si (silicon), Fe (iron), Zr (zirconium), Mn (manganese), Mg (magnesium), Ca (calcium), and Zn (zinc). Among them, it is preferable to contain one or more elements selected from Al (aluminum), Zn (zinc), Mg (magnesium), Ca (calcium), Ti (titanium), Ba (barium), O (oxygen), P (phosphorus), and S (sulfur), and it is particularly preferable to contain O (oxygen) and / or P (phosphorus) and one or more elements selected from Al (aluminum), Zn (zinc), Mg (magnesium), Ca (calcium), Ti (titanium), and Ba (barium).

[0023] Examples of activators for the inorganic fluorescent powder a) including the activator used in the present invention include, but are not limited to, Mn (manganese), Eu (europium), Cr (chromium), Ce (cerium), Pr (praseodymium), La (lanthanum), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), Fe (iron), Zn (zinc), Ti (titanium), and the like.

[0024] The inorganic fluorescent powder a) used in the present invention preferably contains, as a crystal host and / or activator, at least one element selected from Al (aluminum), Zn (zinc), Mg (magnesium), Si (silicon), Mn (manganese), Ca (calcium), Ti (titanium), Ce (cerium), Ba (barium), O (oxygen), P (phosphorus), and S (sulfur), with (Al / Ca / manganese) oxide, (Mg / manganese / titanium) oxide, zinc oxide phosphor, and (Ca / cerium) phosphate being particularly preferred.

[0025] The inorganic fluorescent powder a) used in the present invention may be one that emits fluorescence of any color, and red fluorescent powder, green fluorescent powder, and blue fluorescent powder are particularly preferred.

[0026] a) The maximum fluorescent wavelength of the inorganic fluorescent powder is preferably in the range of 440 nm to 520 nm or 640 nm to 700 nm.

[0027] Examples of commercially available inorganic fluorescent powder a) used in the present invention include Lumate R (manufactured by Sakai Chemical Industry Co., Ltd.), Lumate G (manufactured by Sakai Chemical Industry Co., Ltd.), Lumate B (manufactured by Sakai Chemical Industry Co., Ltd.), etc., but are not limited to these.

[0028] The particle size of the inorganic fluorescent powder a) used in the present invention is not particularly limited, but is preferably 0.5 μm or more, and more preferably 1 μm or more. The particle size of the inorganic fluorescent powder a) is 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. The particle size of the inorganic fluorescent powder a) used in the present invention is preferably 1 μm or more and 200 μm or less, and more preferably 2 μm or more and 100 μm or less, from the viewpoints of obtaining sufficient fluorescent intensity and excellent usability when used in cosmetics, etc.

[0029] The particle size used in the present invention refers to the average size of primary particles when observed with a transmission electron microscope.

[0030] The non-fluorescent powder b) used in the present invention is not particularly limited as long as it is a powder that does not have fluorescent properties, and may be an inorganic or organic powder, and there is no limitation on the shape or size.

[0031] Examples of inorganic powders include, but are not limited to, titanium oxide, non-fluorescent zinc oxide, iron oxide (red ocher, yellow iron oxide, black iron oxide), silica, aluminum oxide, aluminum hydroxide, cesium oxide, chromium oxide, chromium hydroxide, barium sulfate, synthetic phlogopite, mica, talc, sericite, kaolin, gunjo, konjo, carbon black, calcium carbonate, magnesium carbonate, silicone, magnesium silicate, magnesium aluminum silicate, and boron nitride.

[0032] Commercially available inorganic powders include, for example, MP-1133AQ (manufactured by Teika Corporation), MP-1133WP (manufactured by Teika Corporation), MT-100WP (manufactured by Teika Corporation), MT-100SA (manufactured by Teika Corporation), MT-500B (manufactured by Teika Corporation), MZ-300 (manufactured by Teika Corporation), MTZ-3040TSW (manufactured by Teika Corporation), MZ-500 (manufactured by Teika Corporation), FINEX-30 (manufactured by Sakai Chemical Industry Co., Ltd.), FINEX-50 (manufactured by Sakai Chemical Industry Co., Ltd.), FINEX-30W (manufactured by Sakai Chemical Industry Co., Ltd.), FINEX-50W (manufactured by Sakai Chemical Industry Co., Ltd.), FINEX-50W-LP2 (manufactured by Sakai Chemical Industry Co., Ltd.), AEROSIL 200 (manufactured by Nippon Aerosil Co., Ltd.), AEROSIL Alu C (manufactured by Nippon Aerosil Co., Ltd.), LL-100HP (manufactured by Titanium Kogyo Co., Ltd.), R-516HP (manufactured by Titanium Kogyo Co., Ltd.), BL-100HP (manufactured by Titanium Kogyo Co., Ltd.), Sericite FSE (manufactured by Sanshin Mining Co., Ltd.), Silica Microbead P-1500 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), KSP-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), KSP-300 (manufactured by Shin-Etsu Chemical Co., Ltd.), and the like can be mentioned, but are not limited to these.

[0033] Examples of organic powders include, but are not limited to, polyethylene, polyamide, cross-linked polystyrene, polymethyl methacrylate, cellulose, carbamate, fluororesin, polyolefin, epoxy resin, phenolic resin, wheat starch, silk, long-chain fatty acid salts, ceramide, and phospholipids.

[0034] Examples of commercially available organic powders include, but are not limited to, Ganz Pearl GMX-0610 (manufactured by Aica Kogyo Co., Ltd.), Ganz Pearl GMX-0610AQ (manufactured by Aica Kogyo Co., Ltd.), SP-500 (manufactured by Toray Industries, Inc.), Ceramide I (manufactured by Evonik), Ceramide III (manufactured by Evonik), Ceramide VI (manufactured by Evonik), Phytopresome Care-V (manufactured by Nippon Fine Chemicals Co., Ltd.), Ceramide TIC-001 (manufactured by Takasago International Corporation), SLP-PC70 (manufactured by Tsuji Oil Milling Co., Ltd.), SLP-PC92H (manufactured by Tsuji Oil Milling Co., Ltd.), and NIKKOL Resinol S-10 (manufactured by Nikko Chemicals Co., Ltd.).

[0035] The non-fluorescent powder used in the present invention is preferably an inorganic powder, and among these, metal oxides, metal hydroxides, and silicates are preferred, with metal oxides and silicates being more preferred, and titanium oxide, non-fluorescent zinc oxide, iron oxide, aluminum oxide (alumina), and silica being particularly preferred.

[0036] In addition, the particle size of the non-fluorescent powder b) used in the present invention is preferably smaller than the particle size of the inorganic fluorescent powder used in the present invention, and is preferably 250 nm or less, and more preferably a fine particle of 100 nm or less. In addition, from the viewpoint of the effect of improving the fluorescence intensity of the composite particle of the present invention, it is preferably 0.1 nm or more, and more preferably 1 nm or more. The particle size of the non-fluorescent powder used in the present invention is preferably 0.1 nm or more and 150 nm or less, and more preferably 1 nm or more and 100 nm or less.

[0037] The a) inorganic fluorescent powder and / or b) non-fluorescent powder used in the present invention may be surface-treated depending on the combination of powders to be composited in order to improve adhesion between the powders, to increase the fluorescence intensity of the composite powder obtained, etc. This surface treatment may be performed on each powder before composite, or on the composite powder obtained.

[0038] The types of substances used for surface treatment include, but are not limited to, silica, alginic acid, aluminum oxide (alumina), POE / dimethicone copolymer, polyethylene glycol, aluminum hydroxide, amino acids, metal soaps, perfluoroalkylethyl phosphate ester diethanolamine acid, fluoroalkyl acrylate / polyalkylene glycol acrylate polymer, perfluoropolyether phosphoric acid, anionic or cationic polymers having perfluoropolyether chains, hydrogenated lecithin, acylated amino acids, α-tocopherol phosphate ester acid, methylhydrogenpolysiloxane, α-monoalkoxypolydimethylsiloxane, α-dialkoxypolydimethylsiloxane, triethoxysilylethyl polydimethylsiloxyethyl dimethicone, amodimethicone, triethoxycaprylylsilane, aminopropyltriethoxysilane, perfluorooctylethyltriethoxysilane, perfluorooctyltriethoxysilane, and the like. Among these, hydrophilic surface treatments are preferred, and silica, alginic acid, aluminum oxide (alumina), POE / dimethicone copolymer, polyethylene glycol, and aluminum hydroxide are particularly preferred.

[0039] In addition, a) the inorganic fluorescent powder and / or b) the non-fluorescent powder may be subjected to multiple surface treatments, and the surface treatment rate (the ratio of the amount of surface treatment agent to the powder) and the surface treatment method are not particularly limited.

[0040] The inorganic fluorescent powder a) and / or non-fluorescent powder b) used in the present invention preferably have a hydrophilic surface in terms of high adhesion in wet processing in the composite powder preparation method described below. Among them, it is preferable that at least one hydrophilic surface treatment is performed, and it is particularly preferable that the outermost surface is subjected to a hydrophilic surface treatment. Here, examples of hydrophilic surface treatment include, but are not limited to, silica, alginic acid, aluminum oxide (alumina), aluminum hydroxide, amino acid, polyethylene glycol, and POE / dimethicone copolymer treatment.

[0041] The method for preparing the composite powder in the present invention is not particularly limited, but a wet treatment is preferred.

[0042] In the wet treatment, it is preferable to disperse a) inorganic fluorescent powder and b) non-fluorescent powder in a dispersion medium and to coat at least a part of the surface of a) inorganic fluorescent powder with b) non-fluorescent powder. It is also preferable to thoroughly disperse a) inorganic fluorescent powder and / or b) non-fluorescent powder by mechanical stirring and crushing force, and specific examples thereof include, but are not limited to, a magnetic stirrer, a mixer, an ultrasonic wave, a homogenizer, a high-pressure homogenizer, a dispersing mixer, a bead mill, a colloid mill, a roller mill, a three-roller mill, a stamp mill, a rod mill, a ball mill, a jaw crusher, a kneader, a planetary mixer, and the like, and two or more of them may be used.

[0043] In addition, a process such as filtration, centrifugation, drying, etc. may be added. The drying method is not particularly limited. The obtained composite powder may be used as a dispersion or a paste, or may be used as a powder.

[0044] The dispersion medium used in the wet treatment is not particularly limited, and examples thereof include water, alcohol, hydrocarbon oil, ester oil, silicone oil, organic solvent, etc., and the dispersion medium may contain components such as surfactants, salts, and chelating agents.

[0045] The dispersion medium used in the wet treatment is preferably a hydrophilic dispersion medium, and preferably contains at least water, for reasons such as improving the adhesive strength between powder particles.

[0046] The weight ratio of a) inorganic fluorescent powder and b) non-fluorescent powder in the composite powder of the present invention may be appropriately adjusted depending on the shape and size of each of a) inorganic fluorescent powder and b) non-fluorescent powder, but a component a (wt%): component b (wt%)=95:5 to 70:30 is preferable, and 90:10 to 70:30 is particularly preferable. The above ratio may be, for example, the ratio of the amounts (wt%) of component a) and component b) charged when preparing the composite powder.

[0047] Since the composite powder of the present invention has a strong fluorescence intensity, it can be suitably used in various types of skin external compositions such as cosmetics. It can also be suitably used in fields such as lighting, play equipment, and paints that can utilize fluorescence.

[0048] <Skin external composition> The composition for external use of the present invention contains the above-mentioned composite powder of the present invention. The composite powder of the present invention has a strong fluorescent intensity and exhibits excellent luminescence and color correction effects, so that the composition for external use of the skin containing the composite powder can be used in general as an external agent for the skin, such as medicines, quasi-drugs, and cosmetics, for the purpose of making scars less noticeable, adjusting the skin color, imparting makeup effects, etc. In particular, since the composite powder has an excellent makeup effect, it can be suitably used as a cosmetic.

[0049] The content of the complex powder in the topical skin composition of the present invention is from 0.0001% by weight to 50% by weight, preferably from 0.001% by weight to 30% by weight, more preferably from 0.01% by weight to 20% by weight, even more preferably from 0.01% by weight to 10% by weight, and particularly preferably from 0.01% by weight to 5% by weight.

[0050] The composition for external use on the skin of the present invention may contain other ingredients in addition to the complex powder of the present invention, provided that the effects of the present invention are not impaired.

[0051] As other components, depending on various purposes, oil, lipophilic nonionic surfactant, hydrophilic nonionic surfactant, other surfactant, metal ion sequestering agent, natural water-soluble polymer, semi-synthetic water-soluble polymer, synthetic water-soluble polymer, inorganic water-soluble polymer, various extracts, various powders, moisturizing components, polyhydric alcohols, scrubbing agents, UV scattering components, astringent components, peptides or derivatives thereof, amino acids or derivatives thereof, cleansing components, keratin softening components, cell activating components, anti-aging components, blood circulation promoting components, whitening components, components having DNA damage prevention and / or repairing effects, anti-inflammatory components, antioxidant components, vitamins, sebum adsorbing components, antibacterial components, and other components may be included within a range that does not impair the effects of the present invention. In the skin topical composition of the present invention, these components may be blended in one or more types in combination. In addition, each of these components is not particularly limited as long as it can be used in the fields of medicines, quasi-drugs, cosmetics, etc., and any one can be appropriately selected and used.

[0052] The skin external composition of the present invention may contain a non-complexed fluorescent powder in addition to the complex powder of the present invention.

[0053] The method for producing the topical skin composition of the present invention is not particularly limited, and the composition can be produced by blending and mixing the essential component, the composite powder of the present invention, and components appropriately selected from the other components listed above, etc., in a conventional manner.

[0054] Specific applications of the skin topical composition of the present invention include, for example, basic cosmetics such as lotion, moisturizing liquid, milky lotion, beauty essence, pack, hand cream, body lotion, body cream, and lip cream; cleansing cosmetics such as face wash, makeup remover, and body shampoo; makeup cosmetics such as foundation, makeup base, eye color, eye shadow, eye liner, eyebrow, highlight, control color, blush, mascara, lipstick, and face powder; and sunscreen cosmetics. In addition, multifunctional preparations that combine the functions of these cosmetics into one preparation are also included. Furthermore, the composition can be used in pharmaceuticals and quasi-drugs such as wound ointments and topical agents for acne.

[0055] Among these, makeup cosmetics such as foundations, makeup bases, eye colors, eye shadows, eyeliners, eyebrows, highlighters, control colors, blushes, mascaras, lipsticks, and face powders; and sunscreen cosmetics and other cosmetics are particularly preferred.

[0056] <Method for enhancing the fluorescence intensity of inorganic fluorescent powder> The present invention also includes a method for enhancing the fluorescence intensity of an inorganic fluorescent powder, characterized in that a) a portion of the surface of an inorganic fluorescent powder is coated with b) a non-fluorescent powder. Furthermore, the composite powder of the present invention obtained by coating a portion of the surface of an inorganic fluorescent powder with b) a non-fluorescent powder exhibits excellent luminescence, and therefore, when contained in a cosmetic product, a cosmetic product with a stronger makeup effect can be provided. Note that the explanations of a) the inorganic fluorescent powder and b) the non-fluorescent powder in the method for enhancing the fluorescence intensity of an inorganic fluorescent powder and the specific explanation of the composite powder prepared using these powders can be found in the "Composite Powder" section. EXAMPLES

[0057] Next, a composite powder in which at least a portion of the surface of a) an inorganic fluorescent powder is covered with b) a non-fluorescent powder will be described in detail with examples, but the present invention is not limited to these.

[0058] Example 1 4.5g of silica-treated (Al / Ca / manganese) oxide (plate-shaped, particle size 40μm, aluminum hydroxide treatment 4.5%, silica treatment 1.0%, fluorescence wavelength 660nm) was added to 45.5g of water and thoroughly dispersed with a disper mill to obtain an aqueous dispersion of (Al / Ca / manganese) oxide. Next, 0.5g of alumina-treated fine particle titanium oxide (acicular, particle size 15nm, aluminum hydroxide treatment 6%) was added to 49.5g of water and thoroughly dispersed with a disper mill to obtain an aqueous dispersion of alumina-treated fine particle titanium oxide. The aqueous dispersion of alumina-treated fine particle titanium oxide was mixed with the aqueous dispersion of (Al / Ca / manganese) oxide, thoroughly dispersed with a disper mill, filtered, and dried overnight at 60℃. After drying, the aggregates were crushed with a mill grinder to obtain an inorganic fluorescent composite powder.

[0059] Comparative Example 1 An inorganic fluorescent powder mixture was obtained by grinding 4.5 g of silica-treated (Al / Ca / manganese) oxide (plate-shaped, particle size 40 μm, 4.5% aluminum hydroxide treatment, 1.0% silica treatment, fluorescent wavelength 660 nm) and 0.5 g of alumina-treated titanium dioxide fine particle (acicular, particle size 15 nm, 6% aluminum hydroxide treatment) in a mill grinder.

[0060] Comparative Example 2 As Comparative Example 2, silica-treated oxide (Al / Ca / manganese) (plate-like, particle size 40 μm, aluminum hydroxide treatment 4.5%, silica treatment 1.0%, fluorescence wavelength 660 nm) was used.

[0061] <Confirmation of decomposition> A scanning electron microscope VE-8800 (manufactured by Keyence Corporation) was used to observe the inorganic fluorescent composite powder of Example 1 and the inorganic fluorescent powder mixture of Comparative Example 2. Micrographs of each are shown in FIG. 1 (Example 1) and FIG. 2 (Comparative Example 2).

[0062] Comparing Figures 1 and 2, it is clear that in Example 1, alumina-treated titanium dioxide microparticles adhere to the surface of the silica-treated oxide (Al / Ca / manganese), and that the alumina-treated titanium dioxide microparticles, which are non-fluorescent powders, cover the surface of the silica-treated oxide (Al / Ca / manganese), which is an inorganic fluorescent powder.

[0063] <Test 1: Evaluation of fluorescence intensity> Double-sided tape was applied to a plate (50mm x 50mm HELIOPLATE HD6, HelioScreen Labs), and the sample was applied evenly with a brush. Using a spectroscopic variable-angle colorimeter GC-5000 (Nippon Denshoku Industries Co., Ltd.), light was applied to the side of the plate on which the sample was applied at an incident angle of 45°, and the reflection intensity at the regular reflection angle was measured. The intensity at the fluorescence wavelength of the component a) was compared when the intensity when only the inorganic fluorescent powder was present was set to 1.

[0064] [Table 1]

[0065] When comparing the reflection intensity at a fluorescent wavelength of 660 nm between a) inorganic fluorescent powder alone (Comparative Example 2) and a simple mixture of a) inorganic fluorescent powder and b) non-fluorescent powder (Comparative Example 1), the fluorescence intensity increased by about 9 times just by simply mixing a) inorganic fluorescent powder and b) non-fluorescent powder. Example 1: A composite powder of a) inorganic fluorescent powder and b) non-fluorescent powder showed an intensity about 14 times that of Comparative Example 1, and it was confirmed that the fluorescence intensity increased further by the combination.

[0066] In addition, when comparing the fluorescence intensity at a fluorescent wavelength (660 nm) and at a fluorescent wavelength (400 nm), the fluorescence intensity was greater at the fluorescent wavelength (660 nm), and a more significant increase in intensity was confirmed at the fluorescent wavelength of component a). The significant increase in fluorescence intensity at the fluorescent wavelength of 660 nm resulted in a powder with a striking reddish hue.

[0067] Example 2 0.95g of silica-treated (Al / Ca / manganese) oxide (plate-shaped, particle size 40μm, aluminum hydroxide treatment 4.5%, silica treatment 1.0%, fluorescence wavelength 660nm) was added to 49.05g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of (Al / Ca / manganese) oxide. Next, 0.05g of alumina-treated fine particle titanium oxide (acicular, particle size 15nm, aluminum hydroxide treatment 6%) was added to 49.9g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of alumina-treated fine particle titanium oxide. The aqueous dispersion of alumina-treated fine particle titanium oxide was mixed with the aqueous dispersion of (Al / Ca / manganese) oxide, thoroughly dispersed with a Disper Mill, filtered, and dried overnight at 60℃. After drying, the aggregates were crushed with a mill grinder to obtain an inorganic fluorescent composite powder.

[0068] Example 3 0.80 g of silica-treated (Al / Ca / manganese) oxide (plate-shaped, particle size 40 μm, aluminum hydroxide treatment 4.5%, silica treatment 1.0%, fluorescence wavelength 660 nm) was added to 49.20 g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of (Al / Ca / manganese) oxide. Next, 0.20 g of alumina-treated fine particle titanium oxide (acicular, particle size 15 nm, aluminum hydroxide treatment 6%) was added to 49.80 g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of alumina-treated fine particle titanium oxide. The aqueous dispersion of alumina-treated fine particle titanium oxide was mixed with the aqueous dispersion of (Al / Ca / manganese) oxide, thoroughly dispersed with a Disper Mill, filtered, and dried overnight at 60°C. After drying, the agglomerates were crushed with a mill grinder to obtain an inorganic fluorescent composite powder.

[0069] Example 4 0.70g of silica-treated (Al / Ca / manganese) oxide (plate-shaped, particle size 40μm, aluminum hydroxide treatment 4.5%, silica treatment 1.0%, fluorescence wavelength 660nm) was added to 49.30g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of (Al / Ca / manganese) oxide. Next, 0.30g of alumina-treated fine particle titanium oxide (acicular, particle size 15nm, aluminum hydroxide treatment 6%) was added to 49.70g of water and thoroughly dispersed with a Disper Mill to obtain an aqueous dispersion of alumina-treated fine particle titanium oxide. The aqueous dispersion of alumina-treated fine particle titanium oxide was mixed with the aqueous dispersion of (Al / Ca / manganese) oxide, thoroughly dispersed with a Disper Mill, filtered, and dried overnight at 60℃. After drying, the aggregates were crushed with a mill grinder to obtain an inorganic fluorescent composite powder.

[0070] The fluorescence intensities of Examples 1 to 4 which had been subjected to a composite treatment were compared, with the intensity of Comparative Example 2 which was a) inorganic fluorescent powder before composite treatment being set at 1. The results are shown in Table 2.

[0071] [Table 2]

[0072] Example 5 The silica-treated oxide (Al / Ca / manganese) in Example 1 was changed to silica-treated oxide (Al / Ca / manganese) with a particle diameter of 10 μm (plate-like, particle diameter 10 μm, aluminum hydroxide treatment 4.5%, silica treatment 3.0%, fluorescent wavelength 660 nm), to obtain an inorganic fluorescent composite powder.

[0073] Example 6 The silica-treated oxide (Al / Ca / manganese) in Example 3 was changed to silica-treated oxide (Al / Ca / manganese) with a particle diameter of 10 μm (plate-like, particle diameter 10 μm, aluminum hydroxide treatment 4.5%, silica treatment 3.0%, fluorescence wavelength 660 nm), and an inorganic fluorescent composite powder was obtained.

[0074] Example 7 The silica-treated oxide (Al / Ca / manganese) in Example 4 was changed to silica-treated oxide (Al / Ca / manganese) with a particle diameter of 10 μm (plate-like, particle diameter 10 μm, aluminum hydroxide treatment 4.5%, silica treatment 3.0%, fluorescent wavelength 660 nm), to obtain an inorganic fluorescent composite powder.

[0075] Comparative Example 3 As Comparative Example 3, silica-treated oxide (Al / Ca / manganese) (plate-like, particle size 10 μm, aluminum hydroxide treatment 4.5%, silica treatment 3.0%, fluorescence wavelength 660 nm) was used.

[0076] The fluorescence intensities of Examples 5 to 7 which had been subjected to a composite treatment were compared, with the intensity of Comparative Example 3 which was the inorganic fluorescent powder a) before composite treatment being set at 1. The results are shown in Table 3.

[0077] [Table 3]

[0078] From Examples 1 to 4 and Comparative Example 2, it was confirmed that even when the ratio of component a) to component b) was changed, the fluorescence intensity was enhanced by the complexation.

[0079] Moreover, even when the particle size of component a) was changed (Examples 5 to 7), it was confirmed that the fluorescence intensity was enhanced by the complexation. The fluorescence intensity increased significantly especially when the ratio of a:b was 90:10 to 70:30.

[0080] Example 8 The silica-treated oxide (Al / Ca / manganese) in Example 1 was changed to alginic acid-treated oxide (Al / Ca / manganese) (plate-like, particle size 40 μm, 3% alginic acid treatment, fluorescent wavelength 660 nm), and an inorganic fluorescent composite powder was obtained.

[0081] Example 9 The alumina-treated titanium dioxide fine particle of Example 8 was changed to silica-treated titanium dioxide fine particle (acicular, particle diameter 15 nm, silica treatment 30%) to obtain an inorganic composite powder.

[0082] Example 10 The alumina-treated fine titanium oxide particles of Example 1 were replaced with alumina (approximately spherical, particle diameter 13 nm, no surface treatment), to obtain an inorganic fluorescent composite powder.

[0083] Example 11 The silica-treated titanium dioxide (Al / Ca / manganese) in Example 1 was changed to alginic acid-treated titanium dioxide (Al / Ca / manganese) (plate-like, particle diameter 40 μm, 1% alginic acid treatment, fluorescent wavelength 660 nm), and the alumina-treated titanium dioxide fine particle was changed to silica (approximately spherical, particle diameter 12 nm, no surface treatment), to obtain an inorganic fluorescent composite powder.

[0084] Example 12 The silica-treated titanium dioxide (Al / Ca / manganese) in Example 3 was changed to alginic acid-treated titanium dioxide (Al / Ca / manganese) (plate-like, particle diameter 40 μm, 1% alginic acid treatment, fluorescent wavelength 660 nm), and the alumina-treated fine particle titanium dioxide was changed to silica-treated pigment-grade titanium dioxide (approximately spherical, particle diameter 250 nm, 2.6% aluminum hydroxide treatment followed by 5.0% silica treatment) to obtain an inorganic composite powder.

[0085] Example 13 The silica-treated pigment-grade titanium dioxide of Example 12 was replaced with POE-dimethicone copolymer-treated fine particle zinc oxide (approximately spherical, particle size 35 nm, 3.6% triethoxycaprylylsilane treatment, 10.0% polyoxyethylene-methylpolysiloxane copolymer treatment), to obtain an inorganic fluorescent composite powder.

[0086] Comparative Example 4 As Comparative Example 4, alginic acid-treated oxide (Al / Ca / manganese) (plate-like, particle size 4 μm, alginic acid treatment 3%, fluorescence wavelength 660 nm) was used.

[0087] Comparative Example 5 As Comparative Example 5, alginic acid-treated oxide (Al / Ca / manganese) (plate-like, particle size 4 μm, alginic acid treatment 1%, fluorescence wavelength 660 nm) was used.

[0088] The inorganic fluorescent composite powders obtained in each Example were compared with the non-composite a) inorganic fluorescent powder, with the fluorescence intensity set at 1, and the results are shown in Table 4 (the intensity ratio was calculated for Examples 8 and 9 with Comparative Example 4, for Example 10 with Comparative Example 2, and for Examples 11 to 13 with Comparative Example 5).

[0089] [Table 4]

[0090] Example 14 The silica-treated oxide (Al / Ca / manganese) in Example 1 was changed to a phosphate (Ca / cerium) (Lumate B (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 460 nm)), to obtain an inorganic fluorescent composite powder.

[0091] Example 15 The silica-treated oxide (Al / Ca / manganese) in Example 1 was changed to a zinc oxide phosphor (Lumate G (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 500 nm)), and the alumina-treated titanium dioxide fine particle was changed to a silica-treated titanium dioxide fine particle (acicular, particle diameter 15 nm, silica treatment 30%), to obtain an inorganic fluorescent composite powder.

[0092] Example 16 The silica-treated oxide (Al / Ca / manganese) in Example 1 was changed to oxide (Mg / manganese / titanium) (Lumate R (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 660 nm)), and the alumina-treated titanium dioxide fine particle was changed to silica-treated titanium dioxide fine particle (acicular, particle diameter 15 nm, silica treatment 30%), to obtain an inorganic fluorescent composite powder.

[0093] Comparative Example 6 In Comparative Example 6, phosphate (Ca / cerium) (Lumate B (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 460 nm)) was used.

[0094] Comparative Example 7 In Comparative Example 7, a zinc oxide phosphor (Lumate G (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 500 nm)) was used.

[0095] Comparative Example 8 In Comparative Example 8, oxide (Mg / manganese / titanium) (Lumate R (manufactured by Sakai Chemical Industry Co., Ltd., maximum fluorescent wavelength 660 nm) was used).

[0096] The results of comparing the fluorescence intensity at 460 nm between Example 14 and Comparative Example 6, the fluorescence intensity at 500 nm between Example 15 and Comparative Example 7, and the fluorescence intensity at 660 nm between Example 16 and Comparative Example 8 are shown in Table 5. In all cases, the intensity ratio was calculated assuming the intensity of the comparative example to be 1.

[0097] [Table 5]

[0098] <Application to cosmetics> Next, examples of formulations of skin external compositions (cosmetics) containing the inorganic fluorescent complex powder will be shown, but the present invention is not limited to these.

[0099] [Powder foundation] Ingredient name Amount [%] Silicone-treated talc residue Fluorine-treated sericite 5 Silicone-treated pigment-grade titanium dioxide 5 Silicone-treated titanium dioxide particles 5 Boron Nitride 3 (Vinyl dimethicone / methicone silsesquioxane) crosspolymer 2 Nylon powder 1 Magnesium stearate 1 Inorganic fluorescent composite powder of Example 1 3 Methylphenylpolysiloxane 7 2-Ethylhexyl paramethoxycinnamate 5 Bis-ethylhexyloxyphenol methoxyphenyl triazine 1 Sorbitan isostearate 0.5 Color pigment (appropriate amount) Preservatives (appropriate amount) Total 100

[0100] A powder foundation with excellent makeup effect was obtained.

[0101] [Loose powder] Ingredient name Amount [%] Silicone-treated talc residue Fluorine-treated sericite 5 Polymethylsilsesquioxane 7 Inorganic fluorescent composite powder of Example 1 5 Silicone-treated pigment-grade titanium dioxide 3 Mica Titanium 3 Color pigment (appropriate amount) Preservatives (appropriate amount) Total 100

[0102] [Makeup base] Ingredient name Amount [%] water residue BG10 1,3-Pentanediol 1 Xanthan gum 0.1 Hydroxypropyl methylcellulose 0.2 (Hydroxyethyl acrylate / Sodium acryloyldimethyltaurate) copolymer 0.5 Polysorbate 60 1.5 Glyceryl Stearate 1.5 2-Ethylhexyl paramethoxycinnamate 8 Isostearic acid treated zinc oxide particles 2 Diethylamino hydroxybenzoic acid hexyl 3 Isononyl isononanoate 3 Methylpolysiloxane 3 Inorganic fluorescent composite powder of Example 3 1 Mica Titanium 1 Color pigment (appropriate amount) Preservatives (appropriate amount) Total 100

[0103] A makeup base with excellent makeup effect was obtained.

[0104] [Sunscreen] Ingredient name Amount [%] Cyclopentasiloxane Residual Methylphenylpolysiloxane 5 2-Ethylhexyl paramethoxycinnamate 6 Bis-ethylhexyloxyphenol methoxyphenyl triazine 3 Isononyl isononanoate 7 Silicone-treated zinc oxide particles 3 Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone 2 Sorbitan Isostearate 1 Inorganic fluorescent composite powder of Example 1 treated with stearic acid 1 water 25 DPG 5 Xanthan gum 0.1 Ethanol 5 Preservatives (appropriate amount) Total 100

[0105] A sunscreen with excellent makeup effect was obtained. [Industrial Applicability]

[0106] According to the present invention, a composite powder can be provided that significantly improves the fluorescence intensity inherent to the inorganic fluorescent powder. In addition, since the composite powder of the present invention exhibits excellent luminescence, various types of cosmetics with higher makeup effects can be provided by being contained in cosmetics. Furthermore, the composite powder can be used not only in cosmetics but also in fields such as lighting, play equipment, and paints.

Claims

1. At least a part of the surface of the inorganic fluorescent powder a) is covered with the non-fluorescent powder b), and the ratio of the inorganic fluorescent powder a) to the non-fluorescent powder b) is component a:component b=90 (wt%):10 (wt%) to 70 (wt%):30 (wt%); b) A composite powder for a composition for external application to the skin, characterized in that the non-fluorescent powder is at least one selected from the group consisting of titanium oxide, non-fluorescent zinc oxide, mica, silica, aluminum oxide, aluminum hydroxide, cesium oxide, barium sulfate, talc, sericite, kaolin, calcium carbonate, magnesium carbonate, silicone, magnesium silicate, magnesium aluminum silicate, boron nitride, polyethylene, polyamide, cross-linked polystyrene, polymethyl methacrylate, cellulose, carbamate, fluororesin, polyolefin, epoxy resin, phenolic resin, wheat starch, silk, long-chain fatty acid salt, ceramide, and phospholipid (provided that a) the inorganic fluorescent powder is a phosphor formed of an oxynitride or a nitride, and Y 3 A 5 O 12 : Ce 3+ (Except for phosphors that are

2. A composite powder for use in a composition for external application to skin according to claim 1, characterized in that the fluorescent wavelength of the inorganic fluorescent powder a) is within the range of 440 nm to 520 nm or 640 nm to 700 nm.

3. A composite powder for topical skin composition as described in claim 1 or 2, characterized in that a) the inorganic fluorescent powder contains at least one element selected from Al (aluminum), Zn (zinc), Mg (magnesium), Si (silicon), Mn (manganese), Ca (calcium), Ti (titanium), Ce (cerium), Ba (barium), O (oxygen), P (phosphorus), and S (sulfur) as a crystal matrix and / or activator.

4. A composite powder for use in a skin topical composition according to any one of claims 1 to 3, characterized in that a) the inorganic fluorescent powder is at least one selected from the group consisting of (Al / Ca / manganese), (Mg / manganese / titanium) oxide, zinc oxide phosphor, and (Ca / cerium) phosphate.

5. 5. A composite powder for use in a skin external composition according to claim 1, wherein the particle size of the inorganic fluorescent powder is from 1 μm to 200 μm.

6. A composite powder for use in a composition for external application to skin according to any one of claims 1 to 5, characterized in that the particle size of the non-fluorescent powder is 1 nm or more and 100 nm or less.

7. A composition for external use on the skin, comprising the complex powder for use in a composition for external use on the skin according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Coated phosphor, light-emitting device with such phosphor and method of making same

    JP2006518398A

  • Wavelength converting member and light-emitting device

    JP2008150518A

  • Cosmetic composition comprising boron nitride complex powder

    JP2011236137A

  • Cosmetics

    JP2014005255A

  • Phosphor body, production method of phosphor body, and LED element

    JP2014201648A